Data from: Molecular characterization of copepod photoreception - Porter, Megan L.; Steck, Mireille; Roncalli, Vittoria; Lenz, Petra H. (Zenodo, 2018)
Copepod crustaceans are an abundant and ecologically significant group whose basic biology is guided by numerous visually guided behaviors. These behaviors are driven by copepod eyes, including naupliar eyes and Gicklhorn's organs, which vary widely in structure and function among species. Yet little is known about the molecular aspects of copepod vision. In this study we present a general overview of the molecular aspects of copepod vision by identifying phototransduction genes from newly generated and publicly available RNA-sequencing data and assemblies from 12 taxonomically diverse copepod species. We identify a set of 10 expressed transcripts that serve as a set of target genes for future studies of copepod phototransduction. Our more detailed evolutionary analyses of the opsin gene responsible for forming visual pigments found that all of the copepod species investigated express two main groups of opsins: middle-wavelength-sensitive (MWS) opsins and pteropsins. Additionally, there is evidence from a few species (e.g., Calanus finmarchicus, Eurytemora affinis, Paracyclopina nana, and Lernaea cyprinacea) for the expression of two additional groups of opsins—the peropsins and rhodopsin 7 (Rh7) opsins—at low levels or distinct developmental stages. An ontogenetic analysis of opsin expression in Calanus finmarchicus found the expression of a single dominant MWS opsin, as well as evidence for differences in expression across development in some MWS, pteropsin, and Rh7 opsins, with expression peaking in early naupliar through early copepodite stages. Copepod phototransduction transcript sequence data Separate nucleotide and amino acid sequence files for each species for contigs identified from RNA-seq assemblies as involved in phototransduction. All files are as fasta, and the transcript identity is indicated in the sequence header. Copepod_phototrans_transcript_seq_data.zip Lernaea cyprinacea trinity assembly Trinity assembly file with all contigs from reassembled Lernaea cyprinacea RNA-seq data. ...